The local area network industry - what price the value of service? - Lim, Hee Joo (2015)
This study of the LAN industry, commissioned by Netband Technology Pte Ltd, documents the steps taken and the insights gained by the project team in exploring the value of customer service in this emerging industry. Market surveys directed at computer vendors, present users and potential users were conducted in pursuit of defining the parameters of Customer Satisfaction. Specifically, it is hoped that possibility of segmenting the user-market may be established. Recommendations of improving service quality are made with reference to the Service Quality Model. The team has also explored the application of the Tradeoff Analysis in determining different levels of price sensitivities exhibited by different user-segments.